OPTIMALISASI BUDIDAYA KEPITING BAKAU SISTEM SILVOFISHERIES SEBAGAI UPAYA PEMBERDAYAAN NELAYAN DI KAWASAN EKOWISATA DEMANG GEDI, PURWOREJO - Hendrayana Hendrayana; Any Kurniawati; Amir Yarkhasy Yuliardi; Kartika Lintang Prameswari; Sherlyta Nisrina Muthi; Abdul Basir (Universitas Mataram, 2026)
The Demang Gedi Forest Farmer Group (KTH) in Gedangan Village, Purwodadi District, Purworejo Regency, is a community group engaged in coastal conservation through mangrove planting, mangrove nurseries, and management of the Demang Gedi tourism area. The group faces challenges related to limited product diversification and suboptimal conservation management, particularly in developing productive activities. To address these issues, a community service program introduced mangrove crab farming using a silvofisheries system, supported by training and workshops on sustainable mangrove management. The program was implemented through preparation, technical training, mentoring, and monitoring–evaluation stages. The results show improvements in both production and management. The group, which previously had no crab cages, now owns two box-type crab cages with 400 boxes and has generated an income of IDR 4,500,000 from mangrove crab cultivation. In addition, group management has improved, with regular activities now conducted to manage crab farming. Further improvements in cage management and water quality are needed to increase future harvest yields.